MEMPERSIAPKAN RISIKO JANGKA PENDEK PERUSAHAAN PROPERTI DAN REAL ESTAT UNTUK MENINGKATKAN KUALITAS KINERJA KEUANGAN BERKELANJUTAN - Kharisma, Tharisya Putri; Sari, Shinta Permata; Kristiyanti, LMS. (Jurnal Akuntansi dan Pajak, 2024)
Financial performance is an analysis used to determine the success of a company from various activities. Every economic activity will be inseparable from risk. This study examines the effect of short-term corporate risk on financial performance. The population in this study are companies listed on the Indonesia Stock Exchange in 2019-2022. The samples used in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2019-2022. Based on the purposive sampling method, 83 samples are obtained that met the predetermined criteria. The type of data used is secondary data. The hypothesis in this study is tested using multiple regression analysis. Based on the results of multiple linear regression analysis, this study concludes that leverage risk, liquidity risk, and credit risk have effect on financial performance.